Herbicides Use by Smallholder Farmers in the Federal Capital Territory, Nigeria - Jackqeline, Mutambara (Asian Journal of Agriculture and Rural Development, 2013)
This study was carried out to investigate the use of herbicides by smallholder farmers in crop production and determine the socio-economic factors that influence adoption of herbicides in the Federal Capital Territory of Nigeria. A structured questionnaire was used to collect data from 451 smallholder farmers randomly selected. Descriptive statistics, factor analysis and regression analysis were used in analyzing the data. Results showed that farmers used manual (50%) and chemical (50%) weed control options. Factor analysis revealed that 10 socio-economic factors related to weed control could represent the initial set of 20 factors without much compromise on quality of data. The extracted factors together with their communalities were; sex (0.69), household size (0.82), education (0.68), distance to extension ((0.86), distance to input supply (0.84), land (0.79), agricultural courses (0.75), farming objective (0.59), knowledge (0.8) and livestock units (0.69). Regressing these extracted factors with use of herbicides revealed that the coefficients of variables representing household size (-0.023), education (0.042), farming objective (-0.008), livestock (0.598) and knowledge (0.037) factors were significant determinants of herbicide use. The study concluded that to induce adoption of herbicides, policy efforts should be directed towards reducing family sizes, knowledge, education, livestock ownership, and commercialization of crop farming by farmers. However there is a need for further analysis to ascertain the social and economic worth of herbicides as an option in weed control.